2013
DOI: 10.1128/aac.00281-13
|View full text |Cite
|
Sign up to set email alerts
|

Multiplex Liquid Chromatography-Tandem Mass Spectrometry Assay for Simultaneous Therapeutic Drug Monitoring of Ribavirin, Boceprevir, and Telaprevir

Abstract: g New directly acting antivirals (DAAs) that inhibit hepatitis C virus (HCV) replication are increasingly used for the treatment of chronic hepatitis C. A marked pharmacokinetic variability and a high potential for drug-drug interactions between DAAs and numerous drug classes have been identified. In addition, ribavirin (RBV), commonly associated with hemolytic anemia, often requires dose adjustment, advocating for therapeutic drug monitoring (TDM) in patients under combined antiviral therapy. However, an assa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 42 publications
0
10
0
Order By: Relevance
“…A review of the literature revealed that CE [15, 16], HPLC [17–21], UPLC–MS/MS [2224], LC–MS/MS [25, 26] and HPTLC [27, 28] methods have been reported for the analysis of RIT, individually or in combination with other drugs. However, a method for the simultaneous determination of OMB, PAR, RIT and DAS has not yet been reported.…”
Section: Introductionmentioning
confidence: 99%
“…A review of the literature revealed that CE [15, 16], HPLC [17–21], UPLC–MS/MS [2224], LC–MS/MS [25, 26] and HPTLC [27, 28] methods have been reported for the analysis of RIT, individually or in combination with other drugs. However, a method for the simultaneous determination of OMB, PAR, RIT and DAS has not yet been reported.…”
Section: Introductionmentioning
confidence: 99%
“…This approach has allowed the setting-up of numerous multiplex assays for the quantification of drugs from the same therapeutic class in a single chromatographic run. This multiplex approach has been applied notably for the simultaneous analysis of antiretroviral agents (in plasma and cells) [40][41][42][43][44], anti-HCV drugs [45], targeted anticancer agents [46], antimalarials [47], antifungals [48], new generation antiepileptics [49], (Figure 2), antibiotics such as several beta-lactams (carbapenems, penicillins, cephalosporins) altogether [50][51][52][53] or combined with other antibiotics classes including linezolid, ciprofloxacin, daptomycin and rifampicin [54][55][56][57][58]. Overall, the main advantages of this approach are: i) a unique sample extraction procedure and short analytical run; ii) time saving through the establishment of simultaneous calibration curves; iii) easy application to blood samples from patients receiving either single-drugs or combination regimens.…”
Section: How To Interpret a Tdm Measurement?mentioning
confidence: 99%
“…Details of the methodology developed to measure plasma concentrations of SOF, based on liquid chromatography coupled with tandem mass spectrometry, will be reported elsewhere (LAD, unpublished data). RBV plasma concentrations were determined using a previously described analytical method [ 14 ]. Cyclosporine trough levels were determined by enzyme multiplied immunoassay on a Cobas Integra® 400 plus system using reagents from Roche Diagnostics (Rotkreuz, Switzerland).…”
Section: Case Presentationmentioning
confidence: 99%